2017
DOI: 10.1038/jp.2017.145
|View full text |Cite
|
Sign up to set email alerts
|

Listeriosis in pregnancy: under-diagnosis despite over-treatment

Abstract: Although 'febrile gastroenteritis' is a poor predictor of listeriosis in pregnancy, fever, premature contractions and inflammatory markers are important risk indices prompting workup and adequate empiric treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 12 publications
0
19
0
1
Order By: Relevance
“…Only 20% of mothers were treated with a penicillin based antibiotic regimen before delivery, indicating the difficulty in the clinical diagnosis of pregnancy associated listeriosis [27].…”
Section: Discussionmentioning
confidence: 99%
“…Only 20% of mothers were treated with a penicillin based antibiotic regimen before delivery, indicating the difficulty in the clinical diagnosis of pregnancy associated listeriosis [27].…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosing Lm infection prior to an adverse event such as stillbirth or preterm birth continues to be difficult and inconsistent based on patient presentation and laboratory results (Charlier et al, 2014). A retrospective study at a hospital in Israel found that listeriosis is simultaneously underdiagnosed and overtreated (Fouks et al, 2018): over the course of five years, more than one hundred pregnant women who received a diagnosis of suspected listeriosis did not subsequently have a Lm+ culture, while 7 patients who had culture-confirmed Lm had not initially received a diagnosis of suspected listeriosis. One of the advantages of our model is that we can assess infection outcomes given a known bacterial quantity and timing of exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Second, non-speci c signs in infected pregnant women would in uence the antibiotic prophylaxis to prevent neonatal listeriosis [22]. Previous studies have showed that adequate maternal antimicrobial treatment before delivery was associated with a signi cant decrease of infants' severity [24,25]. Unfortunately, in our study and others performed in China[18], none of the maternal listeriosis cases received adequate rst-line antimicrobial treatment [9].…”
Section: Discussionmentioning
confidence: 63%
“…The diagnosis of maternal listeriosis would be challenging, apart from nonspeci c obstetrical signs, fever or u-like symptoms are the only clinical signs in infected mothers [24], but they were not always present. In our study, only one patient had u-like symptoms before delivery.…”
Section: Discussionmentioning
confidence: 99%